The Earth's 'missing' niobium may be in the core. - Wade, J; Wood, B (2001)
As the Earth's metallic core segregated from the silicate mantle, some of the moderately siderophile ('iron-loving') elements such as vanadium and chromium are thought to have entered the metal phase, thus causing the observed depletions of these elements in the silicate part of the Earth. In contrast, refractory 'lithophile' elements such as calcium, scandium and the rare-earth elements are known to be present in the same proportions in the silicate portion of the Earth as in the chondritic meteorites-thought to represent primitive planetary material. Hence these lithophile elements apparently did not enter the core. Niobium has always been considered to be lithophile and refractory yet it has been observed to be depleted relative to other elements of the same type in the crust and upper mantle. This observation has been used to infer the existence of hidden niobium-rich reservoirs in the Earth's deep mantle. Here we show, however, that niobium and vanadium partition in virtually identical fashion between liquid metal and liquid silicate at high pressure. Thus, if a significant fraction of the Earth's vanadium entered the core (as is thought), then so has a similar fraction of its niobium, and no hidden reservoir need be sought in the Earth's deep mantle.